2022
DOI: 10.3233/bmr-200253
|View full text |Cite
|
Sign up to set email alerts
|

Chronic low back pain changes the latissmus dorsi and gluteus maximus muscles activation pattern and upward scapular rotation: A cross-sectional study

Abstract: BACKGROUND: Patients with chronic low back pain (LBP) have an impaired dynamic spinal stability, which may lead to arm injuries. OBJECTIVES: To examine the latissimus dorsi and gluteus maximus muscles activation pattern and the upward scapular rotation in patients with chronic LBP. METHODS: Sixty-one right-handed males were divided into two groups: chronic LBP group (n= 31) and healthy controls (n= 30). The electromyography (EMG) activities of the right and left latissimus dorsi and gluteus maximus were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
1
2
1
Order By: Relevance
“…The result of the current study is consistent with the result of the work by Mohamed et al (24) who found increased activation of LD and decreased activation of GMax muscles in subjects with chronic low back pain as compared to controls. Their study, however, measured the activation of muscles on both sides of the body, unlike our study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The result of the current study is consistent with the result of the work by Mohamed et al (24) who found increased activation of LD and decreased activation of GMax muscles in subjects with chronic low back pain as compared to controls. Their study, however, measured the activation of muscles on both sides of the body, unlike our study.…”
Section: Discussionsupporting
confidence: 93%
“…Also, the major difference between this study and their work is that they measured the EMG muscle activity during prone hip extension while in this study we measured the same muscle activities during walking on a treadmill. Increased scapular upward rotation was reported in subjects with chronic low back pain as compared to healthy controls by the work of Mohamed et al (24). Our study, however, did not find a statistically significant difference between groups with a slight increase in the degree of scapular upward rotation measured at 0 and 45 degrees of abduction in subjects with CNSLBP.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The ground electrode was placed on the spinous process of the L2 vertebra. (9,10). Surface electrocardiography adhesive electrodes were used.…”
Section: Procedures For Assessmentmentioning
confidence: 99%